2014
DOI: 10.1038/nature13203
|View full text |Cite
|
Sign up to set email alerts
|

Juno is the egg Izumo receptor and is essential for mammalian fertilization

Abstract: Fertilisation occurs when sperm and egg recognise each other and fuse to form a new, genetically distinct organism. The molecular basis of sperm-egg recognition is unknown, but is likely to require interactions between receptor proteins displayed on their surface. Izumo1 is an essential sperm cell surface protein, but its egg receptor has remained a mystery. Here, we identify Juno as the receptor for Izumo1 on mouse eggs, and show this interaction is conserved within mammals. Female mice lacking Juno are infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
573
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(595 citation statements)
references
References 48 publications
(58 reference statements)
18
573
1
3
Order By: Relevance
“…This figure is modified from [43]. Recently, JUNO was identified as a IZUMO1 interacting factor [5].…”
Section: Resultsmentioning
confidence: 99%
“…This figure is modified from [43]. Recently, JUNO was identified as a IZUMO1 interacting factor [5].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the Izumo1 -/-mice are infertile but izumo1 is not a hub and it belongs to the cluster C. This, in our opinion, could be due to different reasons. First, in many cases our knowledge of molecular interaction of elements involved in SERB is incomplete or in rapid development (see the recent article from Bianchi et al, 2014 describing the interaction of izumo1 with Juno). In addition, our investigations have an intrinsic limit due to the impossibility to analyze the SERBN as a directed network (the networks produced by Agilent Literature Search 3.0.3 beta are undirected).…”
Section: Discussionmentioning
confidence: 99%
“…This sperm‐specific transmembrane protein possesses the IZUMO‐specific domain and immunoglobulin domain. Further observations showed that this protein is originally distributed in the acrosomal principal segment of mature spermatozoa, is translocated to the surface of the equatorial segment during the acrosome reaction,60 and that subsequently the IZUMO1 of the equatorial segment binds to its receptor “JUNO” of the oocyte plasma membrane in the perivitelline space and mediates sperm fusion with the oocyte plasma membrane 61. In the bovine testes (Japanese Black cattle), an ortholog of mouse Izumo1 gene was expressed 62.…”
Section: Acrosomal Proteinsmentioning
confidence: 99%